Targeting Neuroinflammation in Brain Cancer: Uncovering Mechanisms, Pharmacological Targets, and Neuropharmaceutical Developments - Alghamri, Mahmoud S.; McClellan, Brandon L.; Hartlage, Carson S.; Haase, Santiago; Faisal, Syed Mohd; Thalla, Rohit; Dabaja, Ali; Banerjee, Kaushik; Carney, Stephen V.; Mujeeb, Anzar A.; Olin, Michael R.; Moon, James J.; et al. (Frontiers in Pharmacology, 2021)
Gliomas are one of the most lethal types of cancers accounting for 80% of all central nervous system (CNS) primary malignancies [1; 2]. Amongst gliomas, glioblastomas (GBM) are the most aggressive, characterized by a median patient survival of fewer than 15 months. Recent molecular characterization studies uncovered the genetic signatures and methylation status of gliomas and correlate these with clinical prognosis [2]. The most relevant molecular characteristics for the new glioma classification are IDH mutation, chromosome 1p/19q deletion, histone mutations, and other genetic parameters such as ATRX loss, TP53, and TERT mutations, as well as DNA methylation levels. Similar to other solid tumors, glioma progression is impacted by the complex interactions between the tumor cells and immune cells within the tumor microenvironment. The immune system’s response to cancer can impact the glioma’s survival, proliferation, and invasiveness. Salient characteristics of gliomas include enhanced vascularization, stimulation of a hypoxic tumor microenvironment, increased oxidative stress, and an immune suppressive milieu. These processes promote the neuro-inflammatory tumor microenvironment which can lead to the loss of blood-brain barrier (BBB) integrity. The consequences of a compromised BBB are deleteriously exposing the brain to potentially harmful concentrations of substances from the peripheral circulation, adversely affecting neuronal signaling, and abnormal immune cell infiltration; all of which can lead to disruption of brain homeostasis. In this review, we first describe the unique features of inflammation in CNS tumors. We then discuss the mechanisms of tumor-initiating neuro-inflammatory microenvironment and its impact on tumor invasion and progression. Finally, we also discuss potential pharmacological interventions that can be used to target neuro-inflammation in gliomas.